Použití senzoru deformace pro sledování procesu soustružení - Fiala, Josef; Josef Fiala (České vysoké učení technické v Praze, 2024)
Tato bakalářská práce se zabývá monitorováním řezného procesu soustružení senzorem 9232A. Teoretická část je věnována soustružení, řezným podmínkám, silovým jevům při obrábění a jejich monitorováním. Praktická část práce se zabývá monitorováním řezného procesu soustružení senzorem 9232A a porovnáváním dat s dynamometrem. Dále byl řešen piezoelektrický drift a volba vhodné pozice.

This bachelor's thesis deals with monitoring of turning cutting process using sensor 9232A. The theoretical part is dedicated to turning, cutting conditions, force phenomena during machining, and their monitoring. The practical part of the work focuses on monitoring the turning process using the 9232A sensor and comparing the data with a dynamometer. Additionally, the piezoelectric drift and the selection of an appropriate position were addressed.
The use of a deformation sensor for monitoring of the turning process
Keywords: Soustružení; monitorování; řezné síly; senzor; dynamometr; Turning; monitoring; cutting forces; sensor; dynamometer